TOURIST ATTRACTIONS WITH WILD ANIMALS- HIDDEN COST OF TOURIST ENTERTAINMENT - Ćosić, Maja S (The Business of Tourism, 2023)
Besides economic benefits, the development of tourism in a tourist destination should ensure ethical and humane treatment of animals. Wild animals are “tamed” so that they take part in a variety of activities such as: taking photos with tigers, elephant or camel riding, swimming with dolphins, circus performances with bears. However, behind the seemingly appealing activities, there is a hidden, back-stage aspect of the practice. Wild animals are removed from their natural habitat, tamed by various torture methods and exploited. Usually there is a negative impact on their health often resulting in their suffering with possibly fatal consequences. Governments of numerous countries have reacted to such practice with the aim to eradicate it, issuing recommendations either through legislation or through reports compiled by relevant institutions dedicated to the protection of animal rights. In addition, there is a reaction of business entities such as travel agencies, nature parks, hotels and other businesses which offer clear guidance and recommendations, contributing to the education about humane treatment of wild animals.
Keywords: wildlife watching tourism; animal protection; animal suffering; tourist entertainment; exploitation; wildlife conservation